LATE BERRIASIAN–EARLY VALANGINIAN EVOLUTION AND DROWNING OF THE GETIC CARBONATE PLATFORM (SE SERBIA) - Jelena Stefanović; GIOVANNA DELLA PORTA; IOAN I. BUCUR; DEJAN RADIVOJEVIĆ (Rivista Italiana di Paleontologia e Stratigrafia)
The Early Cretaceous was a time of significant development of carbonate platforms on the margins of the Tethys Ocean, including the Getic Carbonate Platform, in the northern peri-Tethys realm, cropping out in the Southern Carpathians (Romania) and Carpatho-Balkanides (Serbia and Bulgaria). This study focusses on the upper Berriasian–lower Valanginian carbonate succession of SE Serbia (Dimitrovgrad) and provides noteworthy insights for the understanding of the Getic Carbonate Platform evolution. On the basis of facies stacking pattern and occurrence of prominent horizons, three vertically superimposed sedimentary units are distinguished in the ~230 m thick succession: unit I consists of shallow subtidal, low-energy environments favouring the development of patch reefs with Bacinella-Lithocodium, rudists, corals, siliceous and calcareous sponges, including stromatoporoids; unit II is indicative of restricted subtidal to intertidal-supratidal facies and platform-top subaerial exposure, testified by karst collapse breccias, syn-sedimentary dolomitization and by negative shifts of carbon and oxygen isotopes; unit III represents the platform drowning stage with abundance of crinoids, chert, detrital quartz and glaucony grains. Platform drowning is marked by a change in carbonate production from photozoan, light-dependent skeletal biota such as corals, to light-independent, filter feeders heterozoan carbonates with crinoids and bryozoans. Syn-sedimentary tectonics appears to be responsible for uplift and subaerial exposure, subsequent rapid deepening and platform demise, possibly associated with increased nutrients during transgression. The Berriasian–Valanginian carbonate strata of Dimitrovgrad show similar evolution to other contemporaneous carbonate systems of western Tethys, highlighting the effects of regional tectonics and global controlling factors on carbonate deposition in the earliest Cretaceous.